2021
DOI: 10.1021/acs.jcim.0c01459
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of the Acid–Base Equilibria in a Model Active Site of the Human 20S Proteasome

Abstract: The 20S Proteasome is a macromolecule responsible for the chemical step in the ubiquitin-proteasome system of degrading unnecessary and unused proteins of the cell. It plays a central role both in the rapid growth of cancer cells as well as in viral infection cycles. Herein, we present a computational study of the acid-base equilibria in an active site of the human proteasome, an aspect which is often neglected despite the crucial role protons play in the catalysis. As example substrates, we take the inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…11,12 Such a large pK a shift would not be unique to this system, with well documented examples in other type of enzymes. 13,14 However, it has recently been shown that the electrostatic interactions with the neighboring E76 play a central role in the proposed activation mechanism. In order to promote a pK a shift at K115, E76 needs also to be protonated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11,12 Such a large pK a shift would not be unique to this system, with well documented examples in other type of enzymes. 13,14 However, it has recently been shown that the electrostatic interactions with the neighboring E76 play a central role in the proposed activation mechanism. In order to promote a pK a shift at K115, E76 needs also to be protonated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To explore the potential of UQ for chemical research, we build upon previous work by Proppe and colleagues, [15,16] addressing Mössbauer spectroscopy, [9,17] dispersion corrections to density functional theory, [18,19] reaction kinetics, [20,21] acid-base equilibria, [22] and exchange spin coupling. [23] This foundation will support our endeavor to pave the way for a novel approach to determining reactivity parameters with steadily increasing accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, just a few attempts were done to study the system using advanced computational techniques. [196][197][198][199][200][201][202] These studies can be classified by the size of the model employed and the computational approach used by the researchers to solve particular problems. Previous studies have been based on two main types of potentials: Mata and co-workers 196,197 reported their results based on QMcluster calculations, and hybrid QM/MM potentials were used with different approaches.…”
Section: Computational Studies Of the 20s Proteasomementioning
confidence: 99%
“…[196][197][198][199][200][201][202] These studies can be classified by the size of the model employed and the computational approach used by the researchers to solve particular problems. Previous studies have been based on two main types of potentials: Mata and co-workers 196,197 reported their results based on QMcluster calculations, and hybrid QM/MM potentials were used with different approaches. Mihalovits et al 198 reported potentials of mean force (PMFs) results corrected by QM-cluster calculations at a higher level of theory; Wei et al [199][200][201] use the FEP methodology for their reported results; and Saha et al 202 use the empirical valence bond (EVB) methodology for obtaining their results.…”
Section: Computational Studies Of the 20s Proteasomementioning
confidence: 99%
See 1 more Smart Citation